2004
DOI: 10.1002/nau.20045
|View full text |Cite
|
Sign up to set email alerts
|

How reliable are bladder perceptions during cystometry?

Abstract: Proprioception of the bladder filling during cystometry is subjective. This data shows that sensations noticed by the patient during filling cystometry may be related to stimuli other than bladder filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…7 This is not surprising since bladder volume is not the sole determinant in the perception of filling as for example localized bladder activity might also play a role. 11 Recently, the validity of the reported sensations during cystometry has been questioned by Erdem et al 9,10 They observed during faked cystometries, that around 80% of the patients spontaneously reported a FSF and FDV and 25% a SDV. Based on these data, they suggested that the reported filling sensations do not depend on the infused volume, and that the evaluation of filling sensations during cystometry is not reliable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 This is not surprising since bladder volume is not the sole determinant in the perception of filling as for example localized bladder activity might also play a role. 11 Recently, the validity of the reported sensations during cystometry has been questioned by Erdem et al 9,10 They observed during faked cystometries, that around 80% of the patients spontaneously reported a FSF and FDV and 25% a SDV. Based on these data, they suggested that the reported filling sensations do not depend on the infused volume, and that the evaluation of filling sensations during cystometry is not reliable.…”
Section: Discussionmentioning
confidence: 98%
“…8 Recently, the validity of the evaluation of filling sensations during cystometry has been challenged by data in two consecutive studies that showed that if patients are told that cystometric bladder filling occurs, more than half of them report desire to void and up to 25% report strong desire to void (SDV) even when the bladder is not filled at all. 9,10 Because such findings may jeopardize the reliability of the evaluation of filling sensation during cystometry in patients with non-neurogenic lower urinary tract dysfunction, we repeated the protocol and evaluated bladder filling sensations during real filling cystometry and during faked cystometry without bladder filling.…”
Section: Introductionmentioning
confidence: 99%
“…By using frequency-volume charts, De Wachter and Wyndaele [12] reported in healthy female students that 65% of all voidings was made without desire to void. More recently, it has been shown that the voiding volume and the desire to void can be manipulated through higher cerebral functioning [13,14] . Thus the BPH patients can cope with the condition of DO by conscious or subconscious behavioral adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly held that normal desire appears at about half capacity, normal desire at two-thirds, and strong desire at near full capacity [Wyndaele, 1991;Van Waalwijk van Doorn et al, 1992]. In a recent report by Erdem et al [2004], the reliability of bladder perception during cystometry was questioned. In this study, a high percentage of patients who had been told what sensations to expect noticed bladder proprioception even though no saline was infused.…”
mentioning
confidence: 97%